Methods to predict the timing and status of biological maturation in male adolescent soccer players: A narrative systematic review. - Joseph Sullivan; Simon J Roberts; John Mckeown; Martin Littlewood; Christopher McLaren-Towlson; Matthew Andrew; Kevin Enright (PLoS ONE)
The aim of this review was to summarise the methods used to predict and assess maturity status and timing in adolescent, male, academy soccer players. A systematic search was conducted on PubMed, Scopus, Web of Science, CINAHL, Medline and SPORTDiscus. Only experimental studies including male, academy players aged U9-U18 years registered with a professional soccer club were included. The methodological quality of the included studies was assessed using guidelines from the Framework of Potential Biases. Fifteen studies fulfilled our inclusion criteria. Studies were mainly conducted in European countries (n = 12). In total, 4,707 players were recruited across all 15 studies, with an age range of 8-18 years. Five studies were longitudinal, two studies were mixed-method designs and eight studies were cross-sectional. Due to high heterogeneity within the studies, a meta-analysis was not performed. Our findings provided no equivalent estimations of adult height, skeletal age, or age at PHV. Discrepancies were evident between actual and predicted adult height and age at PHV. The Bayley-Pinneau [1952], Tanner-Whitehouse 2 [1983] and Khamis-Roche [1994] methods produced estimates of adult height within 1cm of actual adult height. For age at PHV, both Moore [2015] equations produced the closest estimates to actual age at PHV, and the Fransen [2018] equation correlated highly with actual age at PHV (>90%), even when the period between chronological age and age at PHV was large. Medical imaging techniques (e.g., Magnetic Resonance Imaging, X-Ray, Dual energy X-ray Absorptiometry) demonstrated high intra/inter-rater reliability (ICC = 0.83-0.98) for skeletal maturity assessments. The poor concordance between invasive and non-invasive methods, is a warning to practitioners to not use these methods interchangeably for assessing maturational status and timing in academy soccer players. Further research with improved study designs is required to validate these results and improve our understanding of these methods when applied in this target population.